Chitosan copolymer-based coating preservation material as well as preparation method and application thereof
By forming Schiff base imine bonds between chitosan and polylysine and combining with polysaccharide and cellulose nanocrystals to stabilize plant essential oils, composite coating fresh preservation materials were prepared, which solved the problem of the lack of antibacterial and antioxidant of existing packaging materials, and achieved better thermal stability and fresh preservation effects.
Patent Information
- Application Number
- CN202510075145.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing edible food packaging materials lack antibacterial and antioxidant effects, have single functions, insufficient fresh preservation effect, and poor stability of active ingredients in the composite film.
By oxidizing the Schiff alkali imine bond between chitosan and polylysine, combining polysaccharide and cellulose nanocrystals to stabilize plant essential oils, a composite coating fresh preservation material was prepared.
The composite coating material exhibits excellent thermal stability, ultraviolet shielding and visible light transmission performance, water vapor barrier and mechanical properties, and antibacterial properties, which significantly improves the fresh preservation effect of fruits and vegetables.
Smart Images

Figure CN119842080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer material modification, and in particular relates to a chitosan copolymer-based coating fresh-keeping material and a preparation method and application thereof. Background Art
[0002] Food packaging is a coordinated system to ensure the quality, safety and health of food during transportation, distribution, storage and retail until its final use. Traditionally, plastic, paper, glass and metal containers are used to package food. However, the use of these packaging materials will lead to the emission of harmful gases (such as carbon monoxide, hydrochloric acid, chlorine, dioxins, amines, furans, nitrogen compounds, benzene, acetaldehyde, etc.), which will have a serious impact on the environment and endanger human health. In recent years, edible food packaging materials have become a research field.
[0003] Edible food packaging materials refer to the use of natural ingredients such as proteins, polysaccharides, lipids, etc. through different processing techniques, such as coating, dipping, spraying, etc., to form films or coatings with specific functions for food packaging. These edible packaging materials are not only environmentally friendly, but also have certain physical and mechanical properties. They can effectively protect food, and at the same time, they can also delay the migration and diffusion of water, oil and other ingredients in food, and maintain the freshness and quality of food. It can block oxygen from entering food more effectively than common plastic packaging, so it can prevent food from spoiling for a longer period of time and increase the shelf life of food. However, existing edible food packaging materials generally only have physical isolation effects, no antibacterial and antioxidant effects, single functions, and the preservation effect needs to be further improved.
[0004] For example, the Chinese invention patent with application number CN202210225198.8 discloses a method for preparing and applying a natural edible fruit and vegetable fresh-keeping packaging film. The invention patent uses a low eutectic solvent of organic acid and choline chloride to extract apple pomace powder, tea residue powder or turmeric powder by ultrasound-assisted extraction to obtain an extract rich in polyphenols, which is then mixed with an acetic acid solution of chitosan to prepare a fruit and vegetable fresh-keeping packaging film. The natural edible fruit and vegetable fresh-keeping packaging film prepared by this invention patent can prolong the storage time of fruits and vegetables, has low cost, and is safe and environmentally friendly. In addition, the chitosan-based fresh-keeping film loaded with natural polyphenol extracts has good mechanical properties. The Chinese invention patent with application number CN202110635276.7 discloses a degradable cling film and its preparation method and application. The invention uses chitosan-caffeic acid graft copolymer to destroy the dense structure of polylactic acid, thereby improving the air permeability of the degradable cling film, thereby improving the moisture resistance of the degradable cling film, inhibiting the quality deterioration of edible fungi under the packaging of degradable cling film, and extending the shelf life of edible fungi. The Chinese invention patent with application number CN202410291548.X discloses a preparation method and application of a lemon essential oil / rutin / chitosan composite fresh-keeping coating. The invention uses lemon essential oil as the oil phase and rutin and Tween-80 as the water phase. The water and the oil phase are first mixed and homogenized to obtain a crude emulsion. The crude emulsion is ultrasonically treated to prepare a composite nanoemulsion. The composite nanoemulsion and chitosan are prepared in a certain ratio to obtain a composite fresh-keeping coating, which can enhance the antioxidant and antibacterial activity of the chitosan film and effectively extend the shelf life of food.
[0005] However, although the above patents all obtain coating preservation materials by means of composite matching, there are problems such as single coating components and insufficient coating performance. Moreover, the active ingredients in the composite film constructed by simple mixing may lack stability. In addition, although the composite coating preservation materials in the above invention patents are loaded with bioactive substances, the coating materials have insufficient antioxidant capacity and poor preservation effect. Summary of the invention
[0006] The present invention uses chitosan-polylysine Schiff base imine bonds formed between oxidized chitosan (OCS) and polylysine (PL) as a matrix, and uses polysaccharides and cellulose nanocrystals to stabilize plant essential oils to prepare a composite coating preservation material. The composite coating exhibits excellent thermal stability, ultraviolet light shielding and visible light transmission properties, water vapor barrier and mechanical properties, and antibacterial properties, and can be used for post-harvest storage and preservation of tropical fruits.
[0007] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0008] In one aspect, the present invention provides a chitosan copolymer, the structural formula of which is shown below:
[0009] in,
[0010] 20<m<30; 200<n<1000.
[0011] In another aspect, the present invention provides a method for preparing the chitosan copolymer of the present invention, comprising: adding an oxidized chitosan solution to polylysine for polymerization to obtain the chitosan copolymer.
[0012] Preferably, the preparation method satisfies one or more of the following conditions: (i) the preparation method of oxidized chitosan comprises: adding a strong oxidant to a chitosan solution to react and obtain oxidized chitosan; (ii) the oxidized chitosan solution is an oxidized chitosan acetic acid aqueous solution; (iii) the chitosan solution is an oxidized chitosan acetic acid aqueous solution; (iv) the oxidized chitosan solution is adjusted to a pH of 5.0-6.0 and then polylysine is added; (v) the mass ratio of polylysine to oxidized chitosan is 1:1-5:1; (vi) the polymerization reaction temperature is 30°C-60°C; (vii) the polymerization reaction time is 1h-6h.
[0013] More preferably, the preparation method satisfies one or more of the following conditions: (a) the viscosity average molecular weight of chitosan is 1.2×10 3 -2.5×10 5 ; (b) the deacetylation degree of chitosan is ≥80%; (c) the concentration of chitosan is 5mg / mL-20mg / mL; (d) the volume fraction of acetic acid in the oxidized chitosan acetic acid aqueous solution or the chitosan acetic acid aqueous solution is 0.5%-2%; (e) the strong oxidant is one or more combinations of potassium permanganate, sodium periodate, potassium dichromate and potassium chlorate; (f) the mass ratio of the added amount of the strong oxidant to the chitosan) is 0.1mmol / g-10mmol / g; (g) the strong oxidant is added to the chitosan solution for oxidation reaction, and after the oxidation reaction, a terminator is added to terminate the reaction to obtain oxidized chitosan.
[0014] More preferably, the above preparation method satisfies one or more of the following conditions: 1) the oxidation reaction temperature is 30°C-60°C; 2) the oxidation reaction time is 2h-10h; 3) the terminator is one or more of ethylene glycol, glycerol, propylene glycol, and polyethylene glycol; 4) the termination reaction temperature is 30°C-60°C, and the reaction time is 1h-5h.
[0015] In another aspect, the present invention provides a coating preservation material, which comprises a chitosan copolymer film-forming base liquid, a plant essential oil Pickering emulsion, water, nano-enhancing ions and a binder; wherein the chitosan copolymer film-forming base liquid is prepared by adding a plasticizer to the chitosan copolymer of the present invention.
[0016] Preferably, the volume ratio of the plant essential oil Pickering emulsion, water and chitosan copolymer film-forming base liquid is 1:9:10-9:1:10.
[0017] Preferably, the plasticizer is one or more of ethylene glycol, glycerol, sorbitol, polyethylene glycol with a molecular weight less than 5000, ethylenediamine, and triethanolamine; and / or the nano-enhancing ions are cellulose nanocrystals, TiO 2 、Nano-SiO 2 、Nano-CaCO 3 , nano ZnO, nano MgO, nano Au, nano Ag; the binder is one or more of cyclodextrin, oxidized starch, cationic starch, etherified starch, esterified starch, wheat protein, corn protein, gelatin, carrageenan; and / or the plant essential oil is one or more of thyme essential oil, galangal essential oil, tea tree essential oil, lemon essential oil, citronella essential oil, oil peel essential oil, mustard essential oil, peppermint essential oil, cinnamon essential oil, clove essential oil, garlic essential oil, almond essential oil, eucalyptus essential oil, aina essential oil or lavender essential oil.
[0018] Preferably, the plasticizer is added in an amount of 20%-50% of the dry weight of the chitosan copolymer; and / or the nano-enhancing ion is added in an amount of 1%-10% of the dry weight of the chitosan copolymer; and the binder is added in an amount of 0.5%-5% of the dry weight of the chitosan copolymer.
[0019] Preferably, the preparation method of the above-mentioned plant essential oil Pickering emulsion comprises: dispersing polysaccharide and cellulose nanocrystals CNC in a solvent as an emulsifier, then slowly dripping the plant essential oil into the emulsifier, and homogenizing to obtain a Pickering emulsion; ultrasonic emulsification of the Pickering emulsion to obtain the plant essential oil Pickering emulsion; specifically, dispersing polysaccharide and cellulose nanocrystals CNC in a solvent as an emulsifier, then slowly dripping the plant essential oil into the emulsifier dispersion liquid, and homogenizing for 5min-30min at a speed of 10000r / min-15000r / min using a high-speed shearing machine to form a Pickering emulsion in which the polysaccharide and cellulose nanocrystals jointly stabilize the plant essential oil, and then treating the plant essential oil Pickering emulsion with an energy-gathering ultrasonic emulsification disperser; the output power of the ultrasonic treatment is 100W-500W, the ultrasonic time is 5min-15min, and the intermittent pulse working mode is: pulse width 2.0-3s, intermittent time 2.0-5s;
[0020] Preferably, the polysaccharide is one or more of gellan gum GG, carrageenan CAR, konjac gum KG, and gum arabic AG, and the concentration thereof may be 0.1%-2% g / mL; in addition, the concentration of the cellulose nanocrystals may be 0.1%-2% g / mL.
[0021] In another aspect, the present invention provides a use of the chitosan copolymer of the present invention in preparing a coating fresh-keeping material.
[0022] The beneficial effects of the present invention include:
[0023] (1) The antioxidant activity and antibacterial properties of the chitosan copolymer provided by the present invention are significantly improved compared with chitosan or oxidized chitosan.
[0024] (2) The present invention stabilizes the Pickering emulsion of plant essential oil by using polysaccharides in conjunction with cellulose nanocrystals. Compared with the cellulose nanocrystals alone, the emulsion has a higher internal phase ratio and a more uniform particle size distribution.
[0025] (3) The introduction of Pickering emulsion in the present invention can, on the one hand, improve the uniformity of the dispersion of plant essential oils in the membrane matrix and improve the release and stability of the essential oils; on the other hand, the use of polysaccharides and cellulose nanocrystals as emulsion stabilizing particles can give play to the bonding properties of polysaccharides and the reinforcing agent effect of cellulose nanocrystals, which can significantly improve the mechanical properties of the composite membrane.
[0026] (4) The chitosan plant essential oil coating fresh-keeping material prepared by the present invention effectively improves the fresh-keeping effect of the coating material on fruits and vegetables by utilizing the antiseptic property of polylysine and the antibacterial property of plant essential oil, as well as the emulsion stability enhancement effect of polysaccharide and cellulose nanocrystals. The coating material can be applied to fruits and vegetables by convenient spraying or coating, is simple to operate and easy to use, can significantly improve the application efficiency, and reduce the damage to fruits and vegetables. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The infrared spectra (FTIR) of the chitosan and antibacterial chitosan of Example 1 are shown;
[0028] Figure 2 The ultraviolet spectra (UV-vis) of the chitosan and antibacterial chitosan of Example 1;
[0029] Figure 3 The scavenging ability of chitosan and chitosan-polylysine at different concentrations on DPPH free radicals;
[0030] Figure 4 This is an optical microscope photo of the gellan gum GG and cellulose nanocrystals CNC stabilized cinnamon essential oil Pickering emulsion of Example 1;
[0031] Figure 5 This is a particle size distribution diagram of the gellan gum GG and cellulose nanocrystals CNC stabilized cinnamon essential oil Pickering emulsion of Example 1;
[0032] Figure 6 The preservation effect of the antibacterial chitosan copolymers prepared in Example 1 and Example 2 on mangoes; wherein CK is a blank control group (CK), CS is a pure chitosan coating treatment group, and CS-g-PL is an antibacterial chitosan copolymer treatment group;
[0033] Figure 7 The antibacterial chitosan copolymers prepared in Example 3 and Example 4 have a fresh-keeping effect on mangoes. DETAILED DESCRIPTION
[0034] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0035] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0036] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0037] 1. Material preparation and characterization
[0038] Example 1
[0039] (1) Preparation of oxidized chitosan: 1.0 g chitosan (viscosity average molecular weight 2.5 × 10 5 , deacetylation degree ≥ 90%) was dissolved in 100 mL of 0.5% acetic acid aqueous solution (volume fraction, the same below), and then 10 mmol of sodium periodate was added, and stirred for 5 h at 30 ° C in the dark, and the stirring rate was 500 r / min. Then 20 mL of ethylene glycol (0.10 mol / L) was added to the above solution and continued to stir for 1 hour in the dark to terminate the oxidation, and the reaction product was dialyzed in a dialysis bag for 3 days, and finally the dialyzate was freeze-dried for 48 hours to obtain oxidized chitosan (OCS);
[0040] (2) Preparation of antibacterial chitosan copolymer: Weigh 0.5 g of the above-prepared oxidized chitosan (OCS) and dissolve it in 100 mL of 0.5% acetic acid aqueous solution (volume fraction, v / v, the same below), adjust the pH to 6.0, add 0.5 g of polylysine, and stir the reaction at 30°C for 6 hours at a stirring rate of 500 r / min; dialyze the reaction product in a dialysis bag for 3 days, and finally freeze-dry the dialyzate for 48 hours to obtain an antibacterial chitosan copolymer (CS-g-PL).
[0041] First, the structural functional groups of chitosan, oxidized chitosan and antibacterial chitosan copolymers in Example 1 were analyzed by infrared spectrometry (FTIR spectrum can reflect the information of characteristic groups in the composite, and in the infrared spectrum data, the amide I band (1600cm -1 -1700cm -1 ) and amide II bands (1500cm -1 -1560cm -1 ), which is often used to analyze the changes of acylated groups. The infrared characteristic peaks of aldehyde groups mainly include the following positions: C=O stretching vibration of carbonyl group: at 1740~1720cm -1 This is a strong absorption peak in the range of 2820 and 2720 cm-1. -1 Two narrow absorption peaks of medium intensity appear at 2720 cm-1. The high-wavenumber absorption peak is often covered by the CH stretching vibration absorption peak of the saturated methine, so only the absorption peak at 2720 cm-1 is often observed. -1 The absorption peak of chitosan. Therefore, FTIR can be used to reveal the molecular structure of chitosan, oxidized chitosan, and antibacterial chitosan copolymers); the specific steps are as follows: Use a Fourier transform infrared spectrometer (Spectrum3, Platinum Emer) in attenuated total reflection mode to test the infrared spectrum with a spectral resolution of 4 cm -1 , scanning range 4000cm -1 Up to 650cm -1 , 16 times. The infrared spectrum of chitosan and antibacterial chitosan copolymer was scanned to analyze the changes of functional groups. The test results are as follows Figure 1 As shown, chitosan is at 3415, 2953, 2873 cm -1 OH, NH, -CH 2 -Stretching vibration absorption characteristic peaks at 1650 and 1570 cm -1 The characteristic peak of -C=O stretching vibration is 1074cm -1 The characteristic peaks of COC are at 3268, 2922, and 2871 cm-1 OH, NH, -CH 2 -Stretching vibration absorption characteristic peaks, at 1640, 1548cm -1 The stretching vibration characteristic peaks of -C=O, 1062 and 1022 cm -1 The characteristic peaks of COC are at 3360, 3081, 2922, and 2871 cm -1 NH, OH, -CH 2 -, -CH- stretching vibration absorption characteristic peaks; at 1660, 1553cm -1 The stretching vibration characteristic peak at 3360cm -1 A new characteristic peak appeared, which was -NH- stretching vibration, indicating that polylysine and oxidized chitosan were successfully grafted. The above analysis results proved that the antibacterial chitosan copolymer was successfully prepared.
[0042] Secondly, the chitosan and antibacterial chitosan copolymer of Example 1 were analyzed by UV-vis spectrum using a UV-9000S double beam UV-visible spectrophotometer. Figure 2 As shown, (a) is chitosan; (b) is oxidized chitosan; (c) is chitosan-polylysine copolymer; it can be seen that chitosan (a: CS) does not show an absorption peak in the range of 200-400nm, while oxidized chitosan (b: OCS) has an obvious absorption peak at 302nm, which is attributed to the characteristic functional group of oxidized chitosan-CHO; the antibacterial chitosan copolymer (c: CS-g-PL) has obvious absorption peaks at 263nm and 317nm, which are attributed to the characteristic functional group of the newly generated amide group CO-NH.
[0043] Third, chitosan and chitosan-polylysine sample solutions of different concentrations were obtained by diluting with ultrapure water. A certain amount of DPPH powder was weighed and dissolved in anhydrous ethanol to obtain a 0.2 mM DPPH working solution. 1 mL of samples of different concentrations were mixed with an equal volume of DPPH working solution, reacted at 25°C in the dark for 30 minutes, and the absorbance of the mixed solution was measured at 517 nm. The mixed solution of equal volumes of anhydrous ethanol and ultrapure water was adjusted to zero. The absorbance of the mixed solution of the sample and DPPH was As, and the absorbance of the mixed solution of equal volumes of anhydrous ethanol and DPPH was the blank control Ac. The DPPH free radical scavenging rate was calculated using the formula:
[0044]
[0045] The DPPH free radical scavenging rate of Vc was compared and calculated, and the DPPH value of the sample was expressed as μmol Vcequiv. / g.
[0046] Figure 3 The DPPH free radical scavenging ability of chitosan and chitosan-polylysine at different concentrations. It can be seen that the DPPH free radical scavenging ability of chitosan-polylysine is significantly higher than that of chitosan at the same concentration, indicating that the antioxidant capacity of chitosan is significantly improved after modification.
[0047] Example 2
[0048] (1) Preparation of oxidized chitosan: 1.0 g chitosan (viscosity average molecular weight 1.2 × 10 3 , deacetylation degree ≥ 80%) was dissolved in 100 mL of 1.0% acetic acid aqueous solution, and then 0.1 mmol of sodium periodate was added, and stirred at 60°C in the dark for 2 h, with a stirring rate of 500 r / min. Then 20 mL of glycerol (0.10 mol / L) was added to the above solution and stirred for 1 hour in the dark to terminate the oxidation, and the reaction product was dialyzed in a dialysis bag for 3 days, and finally the dialyzate was freeze-dried for 60 h to obtain oxidized chitosan (OCS);
[0049] (2) Preparation of antibacterial chitosan copolymer: Weigh 2.0 g of oxidized chitosan (OCS) and dissolve it in 100 mL of 1.0% acetic acid aqueous solution, adjust the pH to 6.0, add 10.0 g of polylysine, and stir the reaction at 60°C for 1 hour at a stirring rate of 1000 r / min; dialyze the reaction product in a dialysis bag for 3 days, and finally freeze-dry the dialyzate for 60 hours to obtain an antibacterial chitosan copolymer (CS-g-PL).
[0050] Example 3
[0051] (1) Preparation of cinnamon essential oil Pickering emulsion
[0052] Preparation of gellan gum stabilized cinnamon essential oil Pickering emulsion: first take 100 ml of ultrapure water, bathe to 90 degrees, weigh 0.1 g of gellan gum (GG), slowly add 0.1 g of gellan gum while magnetic stirring, fully dissolve for more than 2 hours, add 5 ml of cinnamaldehyde essential oil (CEO) after complete dissolution, and shear at 14000 r / min for 5 minutes to obtain 0.1% GG + 5% cinnamon essential oil emulsion;
[0053] Preparation of cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion: 25 mL of 2% CNC solution was taken, and 75 mL of ultrapure water was added to dilute it to 0.5% CNC. After ultrasonic mixing, 5 mL of cinnamaldehyde essential oil (CEO) was added, and sheared at 14000 r / min for 5 min to obtain 0.5% CNC + 5% cinnamon essential oil emulsion;
[0054] Gellan gum and cellulose nanofibers stabilize cinnamon essential oil Pickering emulsion: first take 50mL of ultrapure water, bathe in water to 90 degrees, weigh 0.1g of gellan gum (GG), slowly add 0.1g of gellan gum while magnetic stirring, fully dissolve for more than 2h, and obtain 0.2% GG solution; then take 25mL of 2% CNC solution, add 25mL of ultrapure water to dilute to 1% CNC, add 5mL of cinnamon essential oil (CEO) under ultrasonic mixing, shear at 14000r / min for 5min to obtain 1% CNC emulsion; mix the CNC emulsion and 0.2% GG solution, and then shear at 14000r / min for 5min to obtain 0.1% GG+0.5% CNC+5% cinnamon essential oil emulsion.
[0055] First, the microscopic morphology of the gellan gum stabilized cinnamon essential oil Pickering emulsion, cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion, and gellan gum synergistic cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion (Example 3) was observed using an inverted optical microscope model EVOS XL Core produced by Thermo Fisher Scientific, USA. Figure 4 As shown (optical micrographs of three different emulsions of gellan gum stabilized cinnamon essential oil Pickering emulsion, cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion and gellan gum synergistically with cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion), the particle size distribution of GG and CNC stabilized cinnamon essential oil Pickering emulsions is relatively uniform, with no obvious aggregation site.
[0056] Second, the particle size distribution of the gellan gum stabilized cinnamon essential oil Pickering emulsion, cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion and gellan gum synergistic cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion of the above (Example 3) was tested by the laser particle size analyzer LT2200E (Zhuhai Zhenli Optical Instrument Co., Ltd.). The results are as follows Figure 5 As shown in the figure, it can be seen that the particle size distribution of the cinnamon essential oil Pickering emulsion stabilized by gellan gum GG and cellulose nanocrystals CNC is relatively uniform and presents a normal distribution; among them, the average particle size of the 5% cinnamon essential oil emulsion stabilized by 0.1% GG is 38.91μm, the average particle size of the 5% cinnamon essential oil emulsion stabilized by 0.5% CNC is 8.76μm, and the average particle size of the 5% cinnamon essential oil emulsion stabilized by 0.1% GG+0.5% CNC is 9.83μm. The above shows that the addition of CNC is beneficial to reducing the average particle size of the GG stabilized emulsion.
[0057] (2) Preparation of chitosan plant essential oil coating preservation materials
[0058] A certain amount of antibacterial chitosan copolymer (CS-g-PL) was weighed and dissolved in an aqueous solution of acetic acid, and 20% (based on the dry weight of CS-g-PL) of glycerol (plasticizer) was added, and the mixture was stirred evenly to prepare a CS-g-PL film-forming base liquid with a concentration of 1% (w / v) (g / mL). 5.0 mL of cinnamon essential oil Pickering emulsion (0.1% GG + 0.5% CNC + 5% cinnamon essential oil emulsion), 45 mL of deionized water and 50 mL of CS-g-PL film-forming base liquid were mixed (emulsion volume: water volume: film-forming liquid volume = 1:9:10), and 1% of nano-TiO based on the dry weight of the film-forming material, i.e., CS-g-PL, was added. 2 (nano-enhanced particles) and 0.5% carrageenan (binder). Then use a high-speed shearing machine to homogenize at a speed of 10000r / min for 3 minutes, and then degas in a vacuum environment for 30 minutes to form an emulsion active film-forming solution with a total volume of 100mL. That is, chitosan plant essential oil coating preservation material.
[0059] Example 4
[0060] (1) Preparation of cinnamon essential oil Pickering emulsion
[0061] Preparation of gellan gum stabilized cinnamon essential oil Pickering emulsion: first take 100 ml of ultrapure water, bathe in water to 90 degrees, weigh 0.4 g of gellan gum (GG), slowly add 0.4 g of gellan gum while magnetic stirring, and fully dissolve for more than 2 hours. After complete dissolution, add 10 ml of cinnamaldehyde essential oil, and shear at 14000 r / min for 5 minutes to obtain 0.4% GG + 10% cinnamon essential oil emulsion.
[0062] Preparation of cellulose nanofiber stabilized cinnamon essential oil Pickering emulsion: Take 50 mL of 2% CNC solution, add 50 mL of ultrapure water to dilute to 1.0% CNC, add 10 mL of cinnamaldehyde essential oil after ultrasonic mixing, and shear at 14000 r / min for 5 min to obtain 1.0% CNC + 10% cinnamon essential oil emulsion.
[0063] Gellan gum and cellulose nanofibers stabilize cinnamon essential oil Pickering emulsion: first take 50mL ultrapure water, bathe to 90 degrees, weigh 0.4g gellan gum (GG), slowly add 0.1g gellan gum while magnetic stirring, fully dissolve for more than 2h, and obtain 0.8% GG solution; then take 50mL 2% CNC solution, ultrasonically mix evenly, add 10mL cinnamaldehyde essential oil, and shear at 14000r / min for 5min to obtain 1% CNC emulsion. Mix 2% CNC emulsion and 0.8% GG solution in equal volumes, and then shear at 12000r / min for 10min to obtain 0.4% GG + 1.0% CNC + 10% cinnamon essential oil emulsion.
[0064] (2) Preparation of chitosan plant essential oil coating preservation materials
[0065] A certain amount of antibacterial chitosan copolymer (CS-g-PL) was weighed and dissolved in an aqueous solution of acetic acid, and 20% (based on the dry weight of CS-g-PL) of glycerol (plasticizer) was added, and the mixture was stirred evenly to form a CS-g-PL film-forming base liquid with a concentration of 1% (w / v) (g / mL). 5.0 mL of cinnamon essential oil Pickering emulsion, 45 mL of deionized water and 50 mL of CS-g-PL film-forming base liquid were mixed (emulsion volume: water volume: film-forming liquid volume = 2:8:10), and 1% of nano-Ag (nano-enhanced particles) and 0.5% of oxidized starch (binder) based on the film-forming material, i.e., the dry weight of CS-g-PL, were added. Then, a high-speed shearing machine was used to homogenize at a speed of 12000 r / min for 5 minutes, and then degassed in a vacuum environment for 30 minutes to form an emulsion active film film-forming solution, and the total volume of the film-forming solution was 100 mL. That is, a chitosan plant essential oil coating preservation material was obtained.
[0066] 2. Verification of the preservation effect of coating preservation materials
[0067] Mangoes with basically the same size, color and maturity and free from pests and diseases and mechanical damage were selected, and were immersed in a 0.05% (v / v) sodium hypochlorite aqueous solution for disinfection for 10 minutes, then washed with distilled water, and naturally dried, and then the mangoes were divided into three groups; wherein, the control group (CK) was not treated in any way; the CS coating group (CS) was immersed in a CS film-forming matrix solution (CS film-forming matrix chitosan was dissolved in a 0.5% (v / v) acetic acid aqueous solution) for 10 minutes, and then taken out to be naturally dried; the chitosan plant essential oil coating preservation material coating group (CS-g-PL) was diluted 100 times with deionized water in Example 1 and Example 2, and then the mangoes were immersed in the film-forming solution for 10 minutes, and then taken out to be naturally dried.
[0068] The mangoes after the above three treatments were placed in a constant temperature and humidity chamber at 25°C and 50% relative humidity for 15 days, and the appearance images were observed. The results are as follows: Figure 6As shown in the figure, at the beginning of storage, the skin color of all mangoes was yellow-green, with no obvious machine damage and pests; on the 5th day, due to the high respiration intensity of the fruit in the CK group, the skin color began to turn yellow. At this time, due to the good barrier properties of the coating, the mango fruits in the CS group and the CS-g-PL group only showed slight yellowing. On the 10th day of storage, obvious black spots appeared on the skin of the mangoes in the CK group, indicating that they had been infected by microorganisms, and the fruit skin showed obvious shrinkage; by the 15th day, a large number of black spots appeared on the surface of the mangoes in the CK group, and they had lost their edible value. Comparing the two groups of coating preservation, a small amount of brown spots appeared on the surface of the fruit in the CS group on the 10th day, and on the 15th day, the brown spots expanded and turned black, indicating that the fruit in the CS group was infected by microorganisms at this time, and the quality began to decline; while the fruit samples in Example 1 and Example 2, except for the slight yellowing of the skin color, a small part of the fruit was infected by microorganisms during the entire storage period, but still had commercial value and nutritional value. The results showed that chitosan copolymer coating can effectively delay the ripening of post-harvest mangoes and extend the shelf life of the fruit.
[0069] In addition, the fresh-keeping effects of the fresh-keeping materials prepared in Examples 3 and 4 were tested according to the above test method. The results are as follows: Figure 7 The surface of mangoes treated with chitosan essential oil coating was glossy throughout the storage period. After 10 days and 15 days of storage, the fruit samples of Example 3 and Example 4 were intact without obvious black spots and rot, and still had commercial value and edible value, indicating that chitosan essential oil coating can also delay the ripening of mangoes after harvest and extend the shelf life of the fruit.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A chitosan copolymer, characterized in that: Its structural formula is as follows: Among them, 20<m<30; 200<n<1000。 2. The method for preparing the chitosan copolymer according to claim 1, characterized in that: include: The oxidized chitosan solution is added into polylysine to carry out polymerization reaction to obtain chitosan copolymer.
3. The preparation method according to claim 2, characterized in that: The preparation method meets one or more of the following conditions: (i) The method for preparing oxidized chitosan comprises: adding a strong oxidant to a chitosan solution to react and obtain oxidized chitosan; (ii) the oxidized chitosan solution is an oxidized chitosan acetic acid aqueous solution; (iii) the chitosan solution is a chitosan acetic acid aqueous solution; (iv) adjusting the pH of the oxidized chitosan solution to 5.0-6.0 and then adding polylysine; (v) the mass ratio of polylysine to oxidized chitosan is 1:1-5:1; (vi) the polymerization temperature is 30°C to 60°C; (vii) The polymerization reaction time is 1 h to 6 h.
4. The preparation method according to claim 3, characterized in that: The preparation method meets one or more of the following conditions: (a) The viscosity average molecular weight of chitosan is 1.2×10 3 -2.5×10 5 ; (b) the deacetylation degree of chitosan is ≥80%; (c) chitosan concentration is 5 mg / mL-20 mg / mL; (d) the volume fraction of acetic acid in the oxidized chitosan acetic acid aqueous solution or the chitosan acetic acid aqueous solution is 0.5%-2%; (e) The strong oxidant is one or more of potassium permanganate, sodium periodate, potassium dichromate and potassium chlorate; (f) the mass ratio of the added amount of the strong oxidant to the chitosan) is 0.1 mmol / g-10 mmol / g; (g) A strong oxidant is added to the chitosan solution to carry out an oxidation reaction, and a terminator is added after the oxidation reaction to carry out a termination reaction to obtain oxidized chitosan.
5. The preparation method according to claim 4, characterized in that: The preparation method meets one or more of the following conditions: 1) The oxidation reaction temperature is 30°C-60°C; 2) The oxidation reaction time is 2h-10h; 3) The terminator is one or more of ethylene glycol, glycerol, propylene glycol, and polyethylene glycol; 4) The termination reaction temperature is 30°C-60°C, and the reaction time is 1h-5h.
6. A coating preservative material, characterized in that: The invention comprises a chitosan copolymer film-forming base liquid, a plant essential oil Pickering emulsion, water, nano-enhancing ions and a binder; wherein the chitosan copolymer film-forming base liquid is prepared by adding a plasticizer to the chitosan copolymer according to claim 1.
7. The coating preservative material according to claim 6, characterized in that: The volume ratio of plant essential oil Pickering emulsion, water and chitosan copolymer film-forming base liquid is 1:9:10-9:1:
10.
8. The coating preservative material according to claim 6 or 7, characterized in that: The coating preservation material meets one or more of the following conditions: ① The plasticizer is one or more of ethylene glycol, glycerol, sorbitol, polyethylene glycol with a molecular weight of less than 5000, ethylenediamine, and triethanolamine; and / or the nano-enhancing ions are one or more of cellulose nanocrystals, TiO2, nano-SiO2, nano-CaCO3, nano-ZnO, nano-MgO, nano-Au, and nano-Ag; the binder is one or more of cyclodextrin, oxidized starch, cationic starch, etherified starch, esterified starch, wheat protein, corn protein, gelatin, and carrageenan; the plant essential oil is one or more of thyme essential oil, galangal essential oil, tea tree essential oil, lemon essential oil, citronella essential oil, oil peel essential oil, mustard essential oil, peppermint essential oil, cinnamon essential oil, clove essential oil, garlic essential oil, almond essential oil, eucalyptus essential oil, aina essential oil, or lavender essential oil; ② The amount of plasticizer added is 20%-50% of the dry weight of the chitosan copolymer; and / or the amount of nano-enhancing ions added is 1%-10% of the dry weight of the chitosan copolymer; the amount of binder added is 0.5%-5% of the dry weight of the chitosan copolymer; ③ The preparation method of the plant essential oil Pickering emulsion comprises: dispersing polysaccharide and cellulose nanocrystals CNC in a solvent as an emulsifier, then slowly dropping the plant essential oil into the emulsifier, and homogenizing to obtain the Pickering emulsion; ultrasonically emulsifying the Pickering emulsion to obtain the plant essential oil Pickering emulsion.
9. The coating preservative material according to claim 8, characterized in that: The polysaccharide is one or more of gellan gum GG, carrageenan CAR, konjac gum KG and gum arabic AG.
10. Use of the chitosan copolymer according to claim 1 in preparing coating fresh-keeping materials.
Citation Information
Patent Citations
A biodegradable food preservation film, its preparation method and application
CN113354930B
Preparation method and application of natural edible fruit and vegetable fresh-keeping packaging film
CN114573884A
Preparation method and application of lemon essential oil / rutin / chitosan composite fresh-keeping coating film
CN118140970A
Dialdehyde chitosan grafted with epsilon-polylysine as well as preparation method and application thereof
CN112851951A
Chitosan-based edible film containing cinnamon oil / cellulose nanocrystals as well as preparation method and application of chitosan-based edible film
CN112961409A
Cited By
Method for integrally preparing chitosan nanofiber / polycaprolactone nanoscale microsphere dispersion as well as product and application thereof
CN121319412A